Less waste has led to improved water quality in Klang River amidst MCO - Kabbashi, Nassereldeen Ahmed (The Malay Mail, 2020)
Also agreeing to the fact that Malaysian rivers are rejuvenating due to the MCO is International Islamic University Malaysia biotechnology engineering lecturer Professor Nassereldeen Ahmed Kabbashi. According to Nassereldeen, because of the MCO, the river's eco-system has been given a chance to recover while multiplying the reproduction of the creatures living in it. “The most important factor which contaminates the rivers is human activities in the form of small, medium and heavy industries production. All carbon monoxide, dioxide, sulphur oxide and such have stopped for a month now.” “This period of no human activities gave a chance for the air and rivers to 'recover'. All rivers must have enough dissolved oxygen, which is considered the secret for rivers to survive. All aquatic life, fish breeding must come now to its normal and better conditions."